Association of myofascial trigger points in neck and shoulder region with depression, anxiety and stress among university students - Muhammad Kashif; Shahira Tahir; Faiqa Ashfaq; Sania Farooq; Wizra Saeed (Journal of the Pakistan Medical Association, 2021)
Objective: To determine the prevalence of myofascial trigger points in the shoulder and neck region, and to assess association with depression, anxiety and stress. Method: The cross-sectional study was conducted from January to September 2019 at Riphah International University, Faisalabad, Pakistan, and comprised students from different universities in Faisalabad. Myofascial trigger points were identified among the subjects using palpation method by a therapist. Depression anxiety stress scale was used to determine the level of depression, anxiety and stress. Data was analysed using SPSS 20. Results: Of the 2000 subjects, 970(49%) were male and 1030(52%) were female. The overall age range was 18-25 years. Myofascial trigger points were present in 1727(86.4%) subjects and absent in 273(13.7%). The trigger points had significant association with depression, anxiety and stress (p<0.001). Conclusion: Myofascial trigger points were quite common among university students and were associated with depression, anxiety and stress. Key Words: Anxiety, Depression, Myofascial trigger points, Myofascial pain syndrome, Stress, Students. Continuous...